2022
DOI: 10.1186/s13054-022-03889-2
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic utility of protein C as a biomarker for adult sepsis: a systematic review and meta-analysis

Abstract: Background Sepsis, the dysregulated host response to infection, triggers abnormal pro-coagulant and pro-inflammatory host responses. Limitations in early disease intervention highlight the need for effective diagnostic and prognostic biomarkers. Protein C’s role as an anticoagulant and anti-inflammatory molecule makes it an appealing target for sepsis biomarker studies. This meta-analysis aims to assess the diagnostic and prognostic value of protein C (PC) as a biomarker for adult sepsis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
(130 reference statements)
0
7
0
1
Order By: Relevance
“…For example, protein C (PC) has a prognostic utility and can serve as a biomarker for adult sepsis prognosis. A meta-analysis showed that PC levels are significantly higher in sepsis survivors compared to non-survivors and in patients with sepsis but not with disseminated intravascular coagulation (DIC) [ 30 ]. Most of the patients in our study displayed significantly higher D-dimer levels, with the highest level being in the severe group, with lower levels of free protein S and higher fibrinogen levels compared to the HC group (mainly in the mild patient group).…”
Section: Discussionmentioning
confidence: 99%
“…For example, protein C (PC) has a prognostic utility and can serve as a biomarker for adult sepsis prognosis. A meta-analysis showed that PC levels are significantly higher in sepsis survivors compared to non-survivors and in patients with sepsis but not with disseminated intravascular coagulation (DIC) [ 30 ]. Most of the patients in our study displayed significantly higher D-dimer levels, with the highest level being in the severe group, with lower levels of free protein S and higher fibrinogen levels compared to the HC group (mainly in the mild patient group).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic monitoring of C-reactive protein, procalcitonin and other inflammationrelated biomarkers are also effective measures to prevent further development of sepsis. [148][149][150][151][152] In fact, in addition to heart-related biomarkers, other biomarkers of organ dysfunction should also be included in the category for comprehensive evaluation because damage to other organs will also result in heart damage. 95 Several novel biomarkers have been developed to identify and track SIMD.…”
Section: Early Identification and Monitoringmentioning
confidence: 99%
“…Although they are controversial, biomarkers for SIMD monitoring are still based on traditional common indicators of myocardial damage, such as cardiac troponin T (cTnT) and cardiac troponin I (cTnI), brain natriuretic peptide, and creatine kinase isoenzyme‐MB. Dynamic monitoring of C‐reactive protein, procalcitonin and other inflammation‐related biomarkers are also effective measures to prevent further development of sepsis 148–152 . In fact, in addition to heart‐related biomarkers, other biomarkers of organ dysfunction should also be included in the category for comprehensive evaluation because damage to other organs will also result in heart damage 95 …”
Section: Treatment Strategiesmentioning
confidence: 99%
“…While the SOFA score is a valuable tool for sepsis evaluation, it involves numerous parameters and indexes, which can be cumbersome during the assessment process. Accordingly, significant efforts have been undertaken to explore new diagnostic techniques and prognostic biomarkers ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%